Summer At Seaside Cove - D'Alessandro, Jacquie; Copyright Paperback Collection (Library of Congress) (New York : Berkley Sensation, 2011)
When Jamie Newman's boyfriend cheats on her with her half-sister, Jamie decides she needs a long vacation. She chooses the island of Seaside Cove, North Carolina, but the accomodations aren't exactly what she expected.
Keywords: Single women -- Fiction; Families -- Fiction; North Carolina -- Fiction; Love stories